APPLICATIONS OF NUMERICAL CLASSIFICATION FOR SOME SOILS OF AL-HASHIMIYA PROJECT IN BABIL PROVINCE - Saleh, A. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Cluster analysis was applied in grouping soils based on their scores of the factors controlling soil variation within 718.326 ha area in Al-Hashimiya District that was located in Babil province. Forty five sites were randomly sampled and analyzed for hierarchical cluster analysis which has been used to group samples by using Ward's method and to develop soil maps. The spatial distribution of distinct groups of elements demonstrates the interplay of ECe, Gypsum content, and particle size distribution factors. Cluster analysis appears to be useful for revealing patterns of soil homogeneity and for identifying relationships among soil properties. Numerical analysis may be a helpful supplementary method for correlating soil surveys with large soil databases.